Islam Unveiled: Dist urbing Questions About the World's Fastest-Growing Faith by Robert Spencer (San Francisco: Encounter Boob???? 2002. 2 I 4 pages.) (American Journal of Islam and Society, 2003)
Rehashing historical animosities, polemics, and stereotypes, Spencer's work is an admirable contribution to the clash of civilizations underway. Basically a collection of diatribes, invective, and ranting against Islam consolidated by a heavy dose of disinformation, Islam Unveiled reflects a discursive piece of work consistent with the lmperium's policies and inter ests. With a pure secular discourse having proven ineffective in confronting Islam, the same discourse has been repackaged in a religious garb, pouring old wine into an even older bottle in order to fight fire with fire. The subtitle of the book, Disturbing Questions About the World's FastestGro-wing Faith, expresses the author's main worries and underscores thatsimilar publications are not mere religio-polemical enterprises to be responded to by sheer counter-polemics. Rather, they are part and parcel of a strategy of conflict seeking to undermine basic beliefs and identity structures for the purpose of essential mastery and domination - military, political, economic, and, above all, cultural. The basic polemical frame is whether and to what possible extent Islam can be made compatible with supposedly "superior" western values. Alternatively, instances in which such compatibility is not possible is taken as a standard point indicating Islamic irrelevance and failure. In the book's IO chapters, therefore, Spencer raises typical questions and issues that, in line with the purposes of western discourse, beg their own answers. Most chapters are in the form of a question probing, for instance, whether Islam is a religion of peace, promotes sound moral values, respects human rights and women, is compatible with liberal democracy or secularism, and is tolerant of others, particularly non-Muslims ...